2018
DOI: 10.1038/s41564-018-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

A type VI secretion system effector delivery mechanism dependent on PAAR and a chaperone–co-chaperone complex

Abstract: The type VI secretion system (T6SS) is used by many Gram-negative bacteria as a molecular weapon to modulate neighbouring bacterial and eukaryotic cells, thereby affecting the dynamics of community structure in multiple species environments. The T6SS injects its inner-needle Hcp tube, the sharpening tip complex consisting of VgrG and PAAR, and toxic effectors into neighbouring cells. Its functions are largely determined by the activities of its delivered effectors. Six mechanisms of effector delivery have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
145
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(152 citation statements)
references
References 41 publications
7
145
0
Order By: Relevance
“…Recently, Burkinshaw et al, described a similar cluster in P. aeruginosa PAO1. They found that TseT, a TOX‐REase‐5 domain‐containing effector, directly interacts with PAAR and the DUF4123 domain‐containing protein for its delivery through the H2‐T6SS (Burkinshaw et al, ). We also found genes encoding predicted triglyceride lipases nearby orphan vgrG genes in most genomes and genes encoding predicted phospholipase D within H2‐T6SS clusters in strains from the P. chlororaphis subgroup (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Burkinshaw et al, described a similar cluster in P. aeruginosa PAO1. They found that TseT, a TOX‐REase‐5 domain‐containing effector, directly interacts with PAAR and the DUF4123 domain‐containing protein for its delivery through the H2‐T6SS (Burkinshaw et al, ). We also found genes encoding predicted triglyceride lipases nearby orphan vgrG genes in most genomes and genes encoding predicted phospholipase D within H2‐T6SS clusters in strains from the P. chlororaphis subgroup (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The VgrG and PAAR proteins play important roles in secretion of T6SS effectors 13,14,16,23 . In NGJ1, we observed either VgrG or PAAR are encoded in the upstream region of various effector operons, indicating that they might act as a carrier for their T6SS mediated delivery (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). The VgrG and PAAR are known to be encoded in some but not all T6SS apparatus encoding gene clusters 23,32,33 .As shown in Fig 1a, the T6SS-2 gene cluster encodes a VgrG protein but lacks PAAR protein, while the T6SS-1 cluster lacks both VgrG and PAAR. Considering this, we hypothesized that effectors which have VgrG (VgrG effector ) encoded in the same operon might be secreted through T6SS-1 while those which are not co-encoded with VgrG would perforce have to be secreted through T6SS-2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations